Tradisi Penentuan Mahar Emas Di Kecamatan Sibolga Selatan - Hasiah, Mufida & (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
Dowry is a valuable symbol for a woman because it is a must. But there are factors that become the tradition of marriage, gold becomes dowry because there are several things that make it imperative, firstly too high prestige that can cause society to use not only a few people but almost the whole, in order to maintain the dignity of the family and maintain a good name, secondly not respected. by other communities to be talked about by other people. This is a social impact that occurs in the community.This research is in the form of field research (Field Research) which is qualitative descriptive field. This research will describe how the tradition of determining the gold dowry in the custom of marriage in the South Sibolga sub-district. Collecting data needed in this research field using interview and observation techniques. While the data analysis technique is carried out by using several steps, namely data editing, data description and drawing conclusions.From the research carried out, the researcher found that the people in the South Sibolga District saw that the dowry was a symbolic value for the prospective bride, such as increasing the self-esteem of a woman, if the community had a high social level, the dowry would increase. And the factors of determining the gold dowry are social status which is often referred to as prestige. All become benchmarks for a person's point of view.